Factors Associated With Long-term Intraocular Pressure Fluctuation in Primary Angle Closure Disease: The CUHK PACG Longitudinal (CUPAL) Study. Issue 8 (August 2018) - Cheung, Carol Y.; Li, Sophia Ling; Chan, Noel; Wong, Mandy Oi-Man; Chan, Poemen Pui-Man; Lai, Isabel; Baig, Nafees; Tan, Shaoying; Man, Xiaofei; Tang, Fangyao; Wang, Yu Meng; Tham, Clement C.
Abstract : Purpose: To determine the demographic, ocular, and systemic factors associated with long-term intraocular pressure (IOP) fluctuation in primary angle closure disease (PACD). Methods: This prospective cohort study included 422 PACD eyes from 269 Chinese patients, including 274 primary angle closure glaucoma (PACG) eyes and 152 primary angle closure/primary angle closure suspect (PAC/PACS) eyes. Long-term IOP fluctuation defined as the SD of all IOP measurements over 2 years (at least 5 measurements in total). Chinese patients with PACD were recruited and followed up 3 monthly. Eyes with IOP-lowering surgery or lens extraction performed within the 2-year study period were excluded. Patient demographics, received treatments, ocular biometry, retinal nerve fiber layer thickness, and systemic factors (eg, hypertension, smoking) were evaluated. Generalized estimating equations adjusting for inter-eye correlation were used to determine the associations. Results: Eyes with PACG had significantly higher IOP fluctuation than PAC/PACS (2.4±1.2 versus 2.1±0.9 mm Hg; P =0.04). In the multivariate analysis with PACG eyes, higher baseline IOP ( P <0.001), greater number of IOP-lowering medications ( P <0.001), previous trabeculectomy ( P =0.002), and current smoking ( P =0.03) were significantly associated with larger IOP fluctuation, whereas diabetes mellitus was associated with lower IOP fluctuation ( P =0.03). Among PAC/PACS eyes, younger age group ( P <0.001), male sex ( P =0.002), and higher baseline IOP ( P <0.001) were significantly associated with larger IOP fluctuation. Conclusions: PACG eyes have greater IOP fluctuation than PAC/PACS eyes. Certain demographic, ocular, and systemic factors are associated with IOP fluctuation in PACD eyes. Abstract : Supplemental Digital Content is available in the text.